Exome sequence analysis and follow up genotyping implicates rare ULK1 variants to be involved in susceptibility to schizophrenia. (17th November 2017) - Al Eissa, Mariam M.; Fiorentino, Alessia; Sharp, Sally I.; O'Brien, Niamh L.; Wolfe, Kate; Giaroli, Giovanni; Curtis, David; Bass, Nicholas J.; McQuillin, Andrew
Summary: Schizophrenia (SCZ) is a severe, highly heritable psychiatric disorder. Elucidation of the genetic architecture of the disorder will facilitate greater understanding of the altered underlying neurobiological mechanisms. The aim of this study was to identify likely aetiological variants in subjects affected with SCZ. Exome sequence data from a SCZ cas–control sample from Sweden was analysed for likely aetiological variants using a weighted burden test. Suggestive evidence implicated the UNC‐51‐like kinase ( ULK1 ) gene, and it was observed that four rare variants that were more common in the Swedish SCZ cases were also more common in UK10K SCZ cases, as compared to obesity cases. These three missense variants and one intronic variant were genotyped in the University College London cohort of 1304 SCZ cases and 1348 ethnically matched controls. All four variants were more common in the SCZ cases than controls and combining them produced a result significant at P = 0.02. The results presented here demonstrate the importance of following up exome sequencing studies using additional datasets. The roles of ULK1 in autophagy and mTOR signalling strengthen the case that these pathways may be important in the pathophysiology of SCZ. The findings reported here await independent replication.